An agentic perspective of resourcefulness: Self-reliant and joint resourcefulness behaviors within the entrepreneurship process - Michaelis, Timothy L.; Scheaf, David J.; Carr, Jon C.; Pollack, Jeffrey M. (Journal of Business Venturing, 2022)
We integrate social cognitive theory, and its tenets of personal and collective agency, to develop an individual-level perspective on entrepreneurs' resourcefulness behaviors that illustrates how resourcefulness behaviors can be classified as ‘self-reliant behaviors’ or ‘joint resourcefulness behaviors’. Using this novel cognitive theoretical approach, we provide and test a framework that explains how dispositional, perceptual, and behavioral factors interact in the enactment of purposeful action with regards to entrepreneurs' resourceful behaviors. Consistent with our hypotheses, results from a quantitative study of entrepreneurs (N = 178), as well as a supplemental study involving qualitative interviews with entrepreneurs (N = 15), highlight that entrepreneurs higher in frugality tend to perceive higher levels of environmental hostility. This relationship, in turn, leads to higher amounts of self-reliant resourcefulness behaviors (i.e., customer-related and internal self-financing bootstrapping behaviors) but not joint resourcefulness behaviors. Multiple theoretical and practical contributions emerge from our findings as the extant literature does not yet account for human agency as a reason why some entrepreneurs may choose to engage in certain resourceful behaviors relative to other behaviors.